ANALYSIS OF LEXICAL AND GRAMATICAL MEANING OF RADHAR PANCA DAHANA'S POLITICAL POETRY OF MANUSIA PALACE BY RADHAR PANCA DAHANA AND IMPLEMENTATION IN LEARNING INDONESIAN LANGUAGE AT HIGH SCHOOL LEVEL - Maulana, Didit; Goziyah, Goziyah; Sulaeman, Agus (Universitas Muhammadiyah Tangerang, 2023)
Based on the results of the research and discussion in CHAPTER IV, it can be concluded that the lexical and grammatical meanings contained in the Collection of Political Poems of Man Palace by Radhar Panca Dahana that, lexical meaning is the meaning of a basic word based on a dictionary, or has a clear meaning. Meanwhile, the grammatical meaning of the meaning process depends on the situation and conditions. From the poems that the researcher has determined to be study material, those that contain lexical and grammatical meanings in the Collection of Human Palace Political Poetry by Radhar Panca Dahana